Primeval - Polone, Gavin; Brancato, John D.; Ferris, Michael; Katleman, Michael (Burbank, CA : Buena Vista Home Entertainment, 2007)
A news team is sent to Africa to capture a twenty-five foot crocodile but find a warlord has put a price on their heads
Features: commentary by director Michael Katleman and visual effects supervisor Paul Linden, documentary, deleted scenes
Title from title screen
Cast: Dominic Purcell, Orlando Jones, Brooke Langton, Jürgen Prochnow
DVD Format
Dolby Digital 5.1
In English, Japanese, Thai, Portugese or Spanish with optional English, Japanese, Thai, Chinese, Indonesian, Malay, Korean, Spanish or Portuguese subtitles
Keywords: Crocodiles -- Drama; Crocodile attacks -- Drama; Television journalists -- Drama